2005
DOI: 10.1113/expphysiol.2005.030551
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the exponential model of body temperature decrease after death in pigs

Abstract: The authors have conducted a systematic study in pigs to verify the models of post-mortem body temperature decrease currently employed in forensic medicine. Twenty-four hour automatic temperature recordings were performed in four body sites starting 1.25 h after pig killing in an industrial slaughterhouse under typical environmental conditions (19.5-22.5• C). The animals had been randomly selected under a regular manufacturing process. The temperature decrease time plots drawn starting 75 min after death for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 16 publications
3
17
1
2
Order By: Relevance
“…The corneal temperature is in fact the surface eye temperature, but can to some extent influence internal eyeball temperature, however the retinal temperature is affected by less than 1.8 8C during an ambient temperature change from À20 8C to +40 8C [10]. The slightly lower (around 1 8C) initial eyeball temperature compared to the core body temperature was also confirmed in pigs [7].…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…The corneal temperature is in fact the surface eye temperature, but can to some extent influence internal eyeball temperature, however the retinal temperature is affected by less than 1.8 8C during an ambient temperature change from À20 8C to +40 8C [10]. The slightly lower (around 1 8C) initial eyeball temperature compared to the core body temperature was also confirmed in pigs [7].…”
Section: Resultssupporting
confidence: 50%
“…The mean value of k c = À0.113 h À1 was determined in studies on pigs eyeballs postmortem cooling process in room temperature 18-22 8C and still air [7][8][9]. Transformation of Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research confi rmed the lack of a plateau effect. It was established that in the case of the use of the eyeball the most reliable results can be obtained during the period up to 13 h after death, whereas in the case of the temperature of the orbital soft tissues the greatest precision is obtained up to 10.5 h after death [31]. This study also found no plateau in the decrease in temperature in the case of the orbital tissues and eyeballs.…”
Section: Discussionsupporting
confidence: 46%
“…Typically the rate of change in temperature varies with time from death and can be described as a monotonic exponential decay for superficial muscles and a sigmoid shape decay for deep muscles in large carcasses (Kaliszan et al 2005). For the latter, the period of temperature inertia at the beginning of the post mortem period is likely due to; (i) metabolic heat production that continues for several hours post mortem and (ii) meat having a relatively low thermal conductivity coefficient that limits the rate of heat movement from within a muscle to the surface.…”
Section: Carcass Coolingmentioning
confidence: 99%